INTRODUCING VARIETIES OF ENGLISHES TO HIGH SCHOOL STUDENTS AT SMA KRISTEN KALAM KUDUS SURAKARTA THROUGH ENGLISH CONVERSATION CLUB - Adaninggar Septi Subekti; Anesti Budi Ermerawati; Ignatius Tri Endarto; Lemmuela Alvita Kurniawati; Mega Wati; Andreas Winardi; Arida Susyetina; Fransisca Endang Lestariningsih (Abdimas Galuh, 2022)
The article reports a community service programme in the form of the English Conversation Club (ECC) for students of Kalam Kudus Senior High School, Surakarta, Central Java. It was conducted in the form of eight 40-50-minute online sessions via Google Meet from January 2022 up to May 2022. 30 students participated in the programme. The programme was mainly designed to introduce the participants to varieties of English such as Tagalog, Korean, Japanese, Australian, and Singaporean Englishes and to describe various places in Indonesia or abroad. Introducing varieties of English, more specifically, was intended to nurture positive attitudes towards varieties of English around the world and local accents with speaking English, including Indonesian accents, which in turn could motivate them to speak English confidently regardless of their accents. The participants reported generally positive attitudes towards the programme even though some participants still saw little relevance as to why they should learn varieties of English other than British and American. This slightly negative attitude may be attributed to the participants' limited previous exposure to varieties of English. The combination of limited duration, a big number of participants, and the online mode of the programme may also lessen the effectiveness and how well the materials on varieties of Englishes were delivered. Based on the limitations, it is suggested that to be more effective, future programmes were designed considering more carefully the duration of each meeting, the number of participants, as well as the participants' level of proficiency and previous background knowledge.